Synthesis, Characterization and DFT Study of 1-(3-Mesityl-3-methylcyclobutyl)-2-((4-phenyl-5-(thiophen-2-yl)-4H-1,2,4-triazol-3-yl)thio)ethan-1-one - Omer, R. A.; Koparir, P.; Koparir, M.; Rashid, R. F.; Ahmed, L. O.; Hama, J. R. (Pleiades Publishing Ltd, 2022)
1-(3-Mesityl-3-methylcyclobutyl)-2-((4-phenyl-5-(thiophen-2-yl)-4H-1,2,4-triazol-3-yl)thio)ethan-1-one was successfully synthesized in this work by condensation of 4-phenyl-5-(thiophen-2-yl)-4H-1,2,4-triazole-3-thiol and 2-chloro-1-(3-mesityl-3-methylcyclobutyl)ethan-1-one with potassium carbonate in the presence of acetone. The compound was characterized experimentally using FT-IR, H-1-, and C-13-NMR spectroscopy as well as elemental analysis. Density Functional Theory (B3LYP/cc-Pvdz) computations were used to analyze the optimal molecular shape, vibrational frequencies, and 1H- and 13C-NMR chemical shifts. The results of theoretical spectroscopy were compared to experimental data. The practical and theoretical results were found to be in agreement, confirming the molecular structure of the created molecule. Dipole moment (mu), hardness (eta), softness (sigma), electronegativity (chi), electrophilicity index (omega), nucleophilicity index (epsilon), and chemical potential (Pi) were among the electronic structural factors connected to corrosion inhibition efficacy are investigated. The fraction of transferred electrons (Delta N) was also calculated to determine the interaction between the iron surface and organic molecules. The calculations show that organic-based corrosion inhibitors and quantum chemical parameters processes have a positive association. Without the necessity for experimental investigation, the behavior of corrosion inhibitors can be predicted.
Keywords: synthesis triazole derivative; IR spectroscopy; NMR spectroscopy; DFT; corrosion study